Designing Progress Tracking System for Laboratory to Promote Effectiveness in Providing Information to Customers - Anastasia L. Maukar; Calvin Tungki Hadinata (President University, 2017)
The main objective of this research is to improve the current flow of information in the laboratory as it is found to be ineffective to reach the customers. This research is necessary and demanded to be finished as soon as possible as it may affect the product development in Toy Manufacturing company. To solve the information flow problem, it is then initiated the idea to develop a new progress tracking system, which is supposed to be able to provide real-time information to customers and make them able to react faster to problems. Lack of information in the problem could lead to longer development lead time. T The researchconducted during the project was basically involving literature review, online journals review, questionnaire, case study, and discussion. This research covers the whole development process of the system, up to theimplementation and evaluation. The result shows that there is improvement of 42.47% in delivering tracking information to the customers.